Impact of deficit irrigation strategies in a saline environment on Shiraz yield, physiology, water use and tissue ion concentration. (25th June 2015) - DeGaris, K.A.; Walker, R.R.; Loveys, B.R.; Tyerman, S.D.
Abstract Background and Aims This study investigated the response of field‐grown Shiraz vines to saline irrigation involving water‐deficit irrigation techniques. Methods and Results Drip‐irrigated Shiraz vines were subjected to control (1.0–2.3 ML/ha), reduced control and partial root zone drying (both approximately 50% less than control) irrigation treatments utilising moderately saline irrigation over three seasons. Grape juice chloride (Cl−) and sodium (Na+) concentration was not affected significantly by irrigation treatment, although it did vary greatly between seasons. Seasonal influence of rainfall was shown to have more of an effect on Na+ concentration in grape juice, while irrigation applied and hence overall salt load impacted more heavily on grape juice Cl−. Partial root zone drying when compared against the controls had reduced stomatal conductance, leaf water potential, berry mass, and yield and pruning mass, while there was no significant effect on TSS (°Brix), pH and titratable acidity. Conclusion In this study, the seasonal variation of rainfall and total irrigation applied played a greater role in altering the concentration of grape juice Cl− and Na+ than the application of irrigation water with the same moderate salinity but with the differing irrigation strategies. Significance of the Study Regions, where water allocation has been reduced and which are relying on a saline irrigation source, have the ability to manage the Cl− and Na+ concentration present in grape juice by having a better understanding of the role season can play and the variability within that season, thereby making more informed decisions on when to apply irrigation.